Resin composition for dispersing cellulose, fiber material, and molding material

By using a specific acrylic resin, including an alkyl (meth)acrylate having an alkyl group having a carbon atom number of 4 or more, and an unsaturated monomer, the resin composition for cellulose dispersion is prepared, which solves the problem of insufficient dispersion of cellulose fibers in low-polar matrix materials, and significantly improves the mechanical strength of the molded product.

CN119923420APending Publication Date: 2025-05-02DIC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380071708.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-06
Filing Date
2023-11-02
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Among the existing fiber-reinforced composite materials, the dispersion of cellulose fibers in low-polar matrix materials is insufficient, resulting in poor mechanical characteristics of the molded product.

Method used

An acrylic resin with an alkyl (meth)acrylate having an alkyl group having 4 or more carbon atoms, an unsaturated dibasic acid, an unsaturated monomer having a ketone group, and (meth)acrylamide as raw materials was used to prepare a resin composition for cellulose dispersion by radical polymerization, thereby significantly improving the dispersion of cellulose and the mechanical strength of the molded product.

Benefits of technology

The dispersion of cellulose and the mechanical strength of the molded product are significantly improved, and molded products with excellent mechanical properties can be made in low-polar matrix materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a resin composition for dispersing cellulose, which is characterized by containing an acrylic resin (A), the acrylic resin (A) contains, as essential raw materials, an alkyl (meth) acrylate (a1) having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers (a2) selected from among unsaturated dibasic acids and unsaturated monomers having a ketone group, and a (meth) acrylamide (a3) having an amide group other than the unsaturated monomer (a2). The content of the alkyl (meth) acrylate (a1) is 20-50% by mass, the content of the unsaturated monomer (a2) is 10-50% by mass, and the content of the (meth) acrylamide (a3) is 30-70% by mass in monomer components that are starting materials of the acrylic resin (A). The resin composition for dispersing cellulose has excellent dispersibility of cellulose, and thus can effectively enhance the mechanical strength of a molded article comprising a matrix resin such as polyethylene and cellulose fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cellulose dispersing resin composition, a fiber material and a molding material. Background Art

[0002] Cellulose nanofibers are natural raw material nanofillers derived from plants. Among biomass fibers, their use in fiber-reinforced composite materials has attracted attention. As a composite material using cellulose nanofibers, a fiber-reinforced composite material containing cellulose fibers in a matrix material has been proposed, wherein the surface of the cellulose fibers is graft-modified by graft polymerization of a polymerizable component in an aqueous system (for example, see Patent Document 1).

[0003] However, since the polarity of the graft component is high in this composite material, when a low-polarity matrix material such as polyolefin is used, there is a problem that the cellulose fibers are not sufficiently dispersed in the matrix material, and the mechanical properties of the molded product are not sufficiently exhibited.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-67817 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An object of the present invention is to provide a cellulose dispersing resin composition, a fiber material, and a molding material, which can provide a molded product containing cellulose fibers and having excellent mechanical strength.

[0009] Means for solving problems

[0010] The present inventors have conducted intensive studies to solve the above problems and, as a result, have found that a resin composition for dispersing cellulose containing a specific acrylic resin having as essential raw materials an alkyl (meth)acrylate having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers selected from an unsaturated dibasic acid and an unsaturated monomer having a keto group, and (meth)acrylamide can provide a molded product having excellent cellulose dispersibility, a high biomass content, and excellent mechanical strength, thereby completing the present invention.

[0011] That is, the present invention relates to the following cellulose dispersion resin composition, characterized in that it contains an acrylic resin (A), wherein the acrylic resin (A) contains as essential raw materials an alkyl (meth)acrylate (a1) having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers (a2) selected from unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide (a3), and in the monomer components as raw materials of the acrylic resin (A), the alkyl (meth)acrylate (a1) accounts for 20 to 50% by mass, the unsaturated monomer (a2) accounts for 10 to 50% by mass, and the (meth)acrylamide (a3) ​​accounts for 30 to 70% by mass.

[0012] Effects of the Invention

[0013] The resin composition for dispersing cellulose of the present invention is excellent in dispersibility of cellulose and can therefore effectively enhance the mechanical strength of a molded article containing a matrix resin such as polyethylene and cellulose fibers. DETAILED DESCRIPTION

[0014] The cellulose dispersing resin composition of the present invention contains an acrylic resin (A), wherein the acrylic resin (A) contains as essential raw materials an alkyl (meth)acrylate (a1) having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers (a2) selected from unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide (a3), wherein among monomer components as raw materials of the acrylic resin (A), the alkyl (meth)acrylate (a1) accounts for 20 to 50% by mass, the unsaturated monomer (a2) accounts for 10 to 50% by mass, and the (meth)acrylamide (a3) ​​accounts for 30 to 70% by mass.

[0015] It should be noted that, in the present invention, the expression "(meth)acrylate" means either or both of "acrylate" and "methacrylate", the expression "(meth)acrylamide" means either or both of "acrylamide" and "methacrylamide", and the expression "(meth)acrylic acid" means either or both of "acrylic acid" and "methacrylic acid". In addition, the alkyl group in the present invention includes a cycloalkyl group.

[0016] The alkyl (meth)acrylate (a1) has an alkyl group having 4 or more carbon atoms. By using the alkyl (meth)acrylate (a1), cellulose dispersibility is excellent even in a low-polarity matrix material. Examples of the alkyl (meth)acrylate (a1) include n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and stearyl (meth)acrylate. Among these, alkyl (meth)acrylates having an alkyl group having 4 to 18 carbon atoms are preferred because they have excellent cellulose dispersibility and further improve the mechanical strength of the molded product. It should be noted that these alkyl (meth)acrylates (a1) may be used alone or in combination of two or more.

[0017] The unsaturated monomer (a2) is one or more monomers selected from unsaturated dibasic acids and unsaturated monomers having a ketone group, and the unsaturated monomer (a2) can react with cellulose. Examples of the unsaturated dibasic acid include maleic acid (anhydride), fumaric acid, and itaconic acid (anhydride). It should be noted that these unsaturated dibasic acids may be used alone or in combination of two or more.

[0018] Examples of the unsaturated monomer having a ketone group include diacetone (meth) acrylamide. The unsaturated monomer having a ketone group may be used alone or in combination of two or more.

[0019] The (meth)acrylamide (a3) ​​may be used alone or in combination of two or more.

[0020] In addition, as the raw material of the acrylic resin (A), other monomers (a4) may be used as needed in addition to the (meth)acrylic acid alkyl ester (a1), the unsaturated monomer (a2) and the (meth)acrylamide (a3).

[0021] Examples of the other monomer (a4) include (meth)acrylic acid, 2-methylaminoethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, glycidyl (meth)acrylate, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-dodecyl acrylamide, N-propoxymethyl acrylamide, (Meth)acrylates having a functional group, such as 6-(meth)acrylamidocaproic acid, (meth)acryloylmorpholine, N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, and N-[2,2-dimethyl-3-(dimethylamino)propyl]acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, diethylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol di(meth)acrylate, styrene, α-methylstyrene, p-methylstyrene, and chloromethylstyrene. It should be noted that these other monomers (a4) may be used alone or in combination of two or more.

[0022] The amount of the alkyl (meth)acrylate (a1) used is 20 to 50% by mass in the monomer components as the raw materials of the acrylic resin (A), and preferably 25 to 40% by mass in view of further improving the cellulose dispersibility and the mechanical strength of the obtained molded article.

[0023] The unsaturated monomer (a2) is used in an amount of 10 to 50% by mass in the monomer component as a raw material of the acrylic resin (A), and preferably 10 to 40% by mass in view of further improving the cellulose dispersibility and the mechanical strength of the obtained molded article.

[0024] The (meth)acrylamide (a3) ​​is used in an amount of 30 to 70% by mass in the monomer components as raw materials of the acrylic resin (A), and preferably 35 to 60% by mass in view of further improving the cellulose dispersibility and the mechanical strength of the obtained molded article.

[0025] In addition, the weight average molecular weight of the acrylic resin (A) is preferably 10,000 to 100,000 from the viewpoint of further improving the dispersibility of cellulose and the mechanical strength of the obtained molded article. Here, the weight average molecular weight is a value obtained by measuring by gel permeation chromatography (hereinafter abbreviated as "GPC") and converting it into polystyrene.

[0026] The acrylic resin (A) can be produced, for example, by radically polymerizing the (meth)acrylic acid alkyl ester (a1), the unsaturated monomer (a2), the (meth)acrylamide (a3), and, if necessary, other monomers (a4) in an organic solvent and / or water in the presence of a polymerization initiator at a temperature of 60 to 140° C.

[0027] As the organic solvent, for example, aromatic solvents such as toluene and xylene; alicyclic solvents such as cyclohexanone; ester solvents such as butyl acetate and ethyl acetate; alcohol solvents such as ethanol, isobutyl alcohol, n-butanol, and isopropyl alcohol; cellosolve solvents such as sorbitol and propylene glycol monomethyl ether acetate; ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone, etc. These solvents may be used alone or in combination of two or more.

[0028] Examples of the polymerization initiator include azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), and azobiscyanovaleric acid; organic peroxides such as tert-butyl peroxypivalate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, di-tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, benzoyl peroxide, and tert-butyl hydroperoxide; and inorganic peroxides such as hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate. These polymerization initiators may be used alone or in combination of two or more. In addition, the polymerization initiator is preferably used in an amount of 0.1 to 10% by mass relative to the total amount of the monomers that are the raw materials of the acrylic resin (A).

[0029] The cellulose dispersion resin composition of the present invention contains the acrylic resin (A) and may be used in combination with polyethylene resins (PE) such as high-density polyethylene (HDPE), low-density polyethylene (LDPE), bio-polyethylene, polypropylene resins (PP), vinyl chloride resins, styrene resins, (meth)acrylic resins, olefin resins such as vinyl ether resins, nylon resins, polyamide resins, polycarbonate resins, polysulfone resins, polyester resins, cellulose resins such as triacetylated cellulose and diacetylated cellulose, polyamide 6 (PA6, ε-caprolactam) as a polyamide resin, etc., as needed. Thermoplastic resins such as polyamide 66 (PA66, polyhexamethylene adipamide), polyamide 11 (PA11, a polyamide obtained by ring-opening polycondensation of undecanoic acid), polyamide 12 (PA12, a polyamide obtained by ring-opening polycondensation of lauryl lactam), compatibilizers, surfactants, polysaccharides such as starches and alginic acid, natural proteins such as gelatin, animal glue, casein, tannins, zeolites, ceramics, metal powders and other inorganic compounds, colorants, plasticizers, fragrances, pigments, flow regulators, leveling agents, conductive agents, antistatic agents, ultraviolet absorbers, ultraviolet dispersants, deodorants and other additives.

[0030] The fiber material of the present invention comprises the cellulose dispersing resin composition and cellulose fibers, and the cellulose fibers are surface-treated with the cellulose dispersing resin composition, thereby achieving excellent dispersibility of the cellulose fibers in the matrix resin.

[0031] The cellulose fibers are preferably cellulose nanofibers (hereinafter, sometimes abbreviated as “CNF”) from the viewpoint of further improving the mechanical strength of the obtained molded article.

[0032] The fiber material can be easily obtained by, for example, subjecting a monomer serving as a raw material of the acrylic resin (A) to the radical polymerization in the presence of CNF.

[0033] The fiber material can be dried, for example, by a drum dryer, a disc dryer, a cone dryer, a spray dryer, a thin film distillation machine, etc., and then pulverized into fine particles by a Henschel mixer or the like, and provided to the molding material.

[0034] The molding material of the present invention contains the above-mentioned fiber material and a thermoplastic resin as a matrix resin. Examples of the above-mentioned thermoplastic resin include polyolefin resins, polycarbonate resins, polyamide resins, polyester resins, epoxy resins, etc. Among these, polyolefin resins are preferred, and polyethylene is more preferred.

[0035] The molding material of the present invention can be obtained by kneading the above-mentioned fiber material and thermoplastic resin by a known kneading method.

[0036] The molding material of the present invention can provide a molded product having excellent mechanical strength and can therefore be used in the production of various molded products.

[0037] Example

[0038] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples.

[0039] (Example 1)

[0040] In a 2.0L reaction vessel equipped with a stirrer, a thermometer, a cooler, and a nitrogen nozzle, 700.0 parts by mass of a CNF aqueous dispersion ("Binfi-S FMa-10010" manufactured by SUGINO, solid content 10.0% by mass) and 700.0 parts by mass of isopropyl alcohol were added, heated to 70°C, and then a mixture of 38.0 parts by mass of acrylamide, 21.0 parts by mass of lauryl methacrylate, 11.0 parts by mass of maleic acid, 70.0 parts by mass of isopropyl alcohol, 0.5 parts by mass of ammonium persulfate, and 70.0 parts by mass of ion exchange water was added dropwise over 1.5 hours. After 3 hours from the completion of the dropwise addition, the mixture was cooled. The nonvolatile content of the obtained fiber material (1) was 8.5% by mass, and the viscosity at 25°C was 265 mPa·s.

[0041] (Example 2)

[0042] In a 2.0L reaction vessel equipped with a stirrer, a thermometer, a cooler, and a nitrogen nozzle, 700.0 parts by mass of a CNF aqueous dispersion ("Binfi-S FMa-10010" manufactured by SUGINO, solid content 10.0% by weight) and 700.0 parts by mass of isopropyl alcohol were added, heated to 70°C, and then a mixture of 28.0 parts by mass of acrylamide, 21.0 parts by mass of lauryl methacrylate, 21.0 parts by mass of diacetone acrylamide, 70.0 parts by mass of isopropyl alcohol, 0.5 parts by mass of ammonium persulfate, and 70.0 parts by mass of ion exchange water was added dropwise over 1.5 hours. After 3 hours from the completion of the dropwise addition, the mixture was cooled. The nonvolatile content of the obtained fiber material (2) was 8.7% by mass, and the viscosity at 25°C was 247 mPa·s.

[0043] (Example 3)

[0044] In a 2.0L reaction vessel equipped with a stirrer, a thermometer, a cooler, and a nitrogen nozzle, 700.0 parts by mass of a CNF aqueous dispersion ("Binfi-S FMa-10010" manufactured by SUGINO, solid content 10.0% by weight) and 700.0 parts by mass of isopropyl alcohol were added, heated to 70°C, and then a mixture of 28.0 parts by mass of acrylamide, 21.0 parts by mass of butyl acrylate, 21.0 parts by mass of diacetone acrylamide, 70.0 parts by mass of isopropyl alcohol, 0.5 parts by mass of ammonium persulfate, and 70.0 parts by mass of ion exchange water was added dropwise over 1.5 hours. After 3 hours from the completion of the dropwise addition, the mixture was cooled. The nonvolatile content of the obtained fiber material (3) was 8.5% by mass, and the viscosity at 25°C was 196 mPa·s.

[0045] (Comparative Example 1)

[0046] In a 2.0 L reaction vessel equipped with a stirrer, a thermometer, a cooler, and a nitrogen nozzle, 700.0 parts by mass of a CNF aqueous dispersion ("Binfi-S FMa-10010" manufactured by SUGINO, solid content 10.0% by weight) and 840.0 parts by mass of ion exchange water were placed, and 2.1 parts by mass of cerium (IV) diammonium nitrate and 70 parts by mass of methyl methacrylate were added thereto, and the mixture was reacted at a temperature of 30° C. for 4 hours. The nonvolatile content of the obtained fiber material (R1) was 8.6% by mass, and the viscosity at 25° C. was 231 mPa·s.

[0047] (Comparative Example 2)

[0048] As the fiber material (R2), a CNF aqueous dispersion ("Binfi-S FMa-10010" manufactured by Sugino, solid content: 10.0% by mass) was used.

[0049] [Manufacturing of molding materials and molded products]

[0050] The fiber material obtained above was dried with a disc dryer, and the dried product and polyethylene powder ("SHC7260" manufactured by Braskem) as a matrix resin were mixed in such a way that the CNF content became 5% by mass. The obtained mixture was melt-kneaded for 10 minutes at 140°C and 200rpm using a small-sized kneading device ("DSM Xplore1 15" manufactured by Rheo-Lab Co., Ltd.) as a kneading device to produce a molding material. The obtained molding material was injection molded using a small-sized injection molding machine (manufactured by Rheo-Lab Co., Ltd.) at a mold temperature of 50°C and a barrel temperature of 150°C to produce a tensile test test piece (length 74mm, width 5mm, thickness 2mm) as a molded product.

[0051] [Evaluation of mechanical strength of molded products]

[0052] The tensile strength and tensile modulus of the obtained tensile test specimens were measured using a tensile testing machine ("AUTOGRAPH AGS-X" manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min, a chuck distance of 50 mm, a temperature of 23° C., and a humidity of 50%.

[0053] Table 1 shows the monomer compositions and evaluation results of the acrylic resins (A) used in Examples 1 to 3 and Comparative Examples 1 and 2.

[0054] [Table 1]

[0055]

[0056] It was confirmed that the molded articles obtained using the cellulose dispersion resin compositions of Examples 1 to 3 of the present invention were excellent in mechanical strength.

[0057] On the other hand, in Comparative Example 1, which is an example in which methyl methacrylate was used as a raw material of the acrylic resin, it was confirmed that the tensile modulus of the molded product was insufficient.

[0058] Comparative Example 2 is an example in which CNF not treated with an acrylic resin was used, and it was confirmed that the tensile modulus of the molded product was insufficient.

Claims

1. A cellulose dispersion resin composition, characterized in that: The invention discloses a method for preparing a polyacrylic acid resin (A) comprising an alkyl (meth)acrylate (a1) having an alkyl group with 4 or more carbon atoms, one or more unsaturated monomers (a2) selected from unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide (a3) ​​as essential raw materials, wherein the alkyl (meth)acrylate (a1) accounts for 20% to 50% by mass, the unsaturated monomer (a2) accounts for 10% to 50% by mass, and the (meth)acrylamide (a3) ​​accounts for 30% to 70% by mass of the monomer components as raw materials of the polyacrylic acid resin (A).

2. A fiber material, characterized in that: The invention comprises the cellulose dispersing resin composition according to claim 1 and cellulose fibers.

3. A forming material, characterized in that: It contains the fiber material according to claim 2 and a thermoplastic resin.

Citation Information

Patent Citations

  • Fiber-reinforced composite material and method for producing the same

    JP2009067817A